In Vivo Monitoring for Regional Changes of Metabotropic Glutamate Receptor Subtype 1 (mGluR1) in Pilocarpine-Induced Epileptic Rat Brain by Small-Animal PET. Issue 1 (December 2017) - Yamasaki, Tomoteru; Fujinaga, Masayuki; Mori, Wakana; Zhang, Yiding; Wakizaka, Hidekatsu; Nengaki, Nobuki; Xie, Lin; Hatori, Akiko; Zhang, Ming-Rong
Abstract Metabotropic glutamate receptor subtype 1 (mGluR1) is a crucial pharmacological target for several central nervous system disorders. In this study, we aimed to monitorin vivo regional changes of mGluR1 related to neuroinflammation in the brains of rats after pilocarpine-induced status epilepticus (PISE) using longitudinal positron emission tomography (PET). PISE was induced in rats by administering lithium chloride, followed by repeated pilocarpine hydrochloride treatments. PET assessments were conducted usingN -[4-[6-(isopropylamino)-pyrimidin-4-yl]-1, 3-thiazol-2-yl]-N -methyl-4-[11 C]methylbenzamide ([11 C]ITDM), a selective radioligand for mGluR1, andN -benzyl-N -[11 C]methyl-2-(7-methyl-8-oxo-2-phenyl-7, 8-dihydro-9H-purin-9-yl)acetamide ([11 C]DAC), a selective translocator protein PET ligand for neuroinflammation monitoring. PET scans were conducted on PISE rats at 1 day (acute), 1 week (subacute) and 3 weeks (chronic) after repeated seizures. PET with [11 C]ITDM showed significant decreases of mGluR1 availability (BPND ) in the thalamus and hippocampus after PISE over the chronic period. Conversely, PET with [11 C]DAC exhibited a significant increase of radioactive uptake in the forebrain after the acute period, especially in the thalamus. These conflicting changes in the thalamus indicated negative correlation. In conclusion, PET with [11 C]ITDM could successfully visualize hippocampal and thalamic declines of mGluR1 related to neuroinflammation, which would help further understanding for mGluR1 functions in neuroexcitotoxicity.